Giant-size x-men: tribute to wein & cockrum ebook - Wein, Len (Giant-Size X-Men: Tribute To Wein & Cockrum (2020)., 2021)
Collects Giant-Size X-Men: Tribute to Wein & Cockrum (2020) #1, Giant-Size X-Men (1975) #1. One comic book changed the face of Marvel Comics forever in 1975! Writer Len Wein and artist Dave Cockrum revamped the X-Men with an international cast including Storm, Nightcrawler, Colossus and Wolverine! This legendary story took fans by storm and set the stage for the X-Men to become the most popular heroes in the Marvel Universe! Now, 36 of Marvel's top artists come together to re-create this epic story, each drawing one pulse-pounding page in tribute to a true Marvel masterpiece! This all-new, all-different tribute is presented alongside Wein and Cockrum's inimitable original — together with behind-the-scenes artwork and more special features — and all on oversized pages that give new meaning to the title "Giant-Size X-Men"!